2014
DOI: 10.1097/aco.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Emergence delirium in children

Abstract: Emergence delirium in children is a frequent but preventable complication. Strategies for prevention and therapy include particularly pain management and medication with alpha-2 agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
4
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(172 citation statements)
references
References 32 publications
1
149
4
18
Order By: Relevance
“…A long duration of surgery, history of social drinking, presence of a gastric tube, chronic lung disease and severe postoperative pain were predictive of emergence agitation. Studies regarding postoperative emergence agitation have evaluated paediatric patients in the operating room or the PACU, [10][11][12] and few have examined adult patients in either setting. The overall incidence of emergence agitation was reported to be 5% in two large-scale PACU-based prospective studies using the Riker sedation-agitation scale and Richmond agitation and sedation scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A long duration of surgery, history of social drinking, presence of a gastric tube, chronic lung disease and severe postoperative pain were predictive of emergence agitation. Studies regarding postoperative emergence agitation have evaluated paediatric patients in the operating room or the PACU, [10][11][12] and few have examined adult patients in either setting. The overall incidence of emergence agitation was reported to be 5% in two large-scale PACU-based prospective studies using the Riker sedation-agitation scale and Richmond agitation and sedation scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has repeatedly reported that sevoflurane is associated with a high incidence (up to 80%) of emergence agitation in children [6]. Furthermore, Dahmani et al [7] has stated that pediatrics undergoing cataract surgery suffered from higher incidence of postoperative emergence agitation compared with other surgeries because of disturbed vision and eye patching upon awaking. Emergence agitation, including restlessness, disorientation, and inconsolable crying, may lead to suture dehiscence and raise intraocular pressure after cataract surgery [8].…”
Section: Introductionmentioning
confidence: 97%
“…The etiology of ED is still unknown but is thought to be multifactorial and to include postoperative pain and the pharmacokinetics and pharmacodynamics of anesthetic agents [4]. Many ED risk factors, such as the child's age, ethnicity, socioeconomic background, temperament, previous hospital experience, anxiety level, and the length and type of procedure, have been reported in previous studies [14789].…”
Section: Discussionmentioning
confidence: 99%
“…If pediatric patients show ED-like behaviors in the PACU, the staff will usually administer sedative or opioid agents to calm them [14]. However, many of the clinical symptoms of ED are similar to those of paradoxical midazolam reactions [256].…”
mentioning
confidence: 99%